Temporal-spatial Characteristics and Ecological Risk Assessment of Pollutants in Surface Sediment in Changdao County - Liming WANG; Juan ZHANG; Yuanjin LIU; Yuanqing MA; Liping YOU; Yuting ZHAO; Jichen LIU; Yanmin QI (Haiyang Kaifa yu guanli, 2023)
Based on data of surface sediment observed in Changdao County, August, 2018, the temporal and spatial characteristic and ecological risk assessment of pollutants in surface sediment were analyzed. The results showed that the contents the average concentrations of sulfide, oil, Cr, Zn, Pb, Cu, As, Cd, Hg and organic carbon were (40.0, 86.8, 38.4, 36.3, 11.2, 15.9, 13.5, 0.146, 0.0211) mg/kg and 0.359 %, respectively. The single factor pollution index p was shown as As, Cr, Cu, Cd, Zn, Pb, organic carbon, oil, sulfide, Hg, and the pollution of heavy metals was more seriously than that of physical and chemical indexes. All stations potential ecological risk were low. Cadmium was determined as the principal ecological risk factor. The contribution rate of Cd to the Hakanson index was 47.0%. Heavy metals and metalloid pollutants of the studied areas mainly came from atmospheric deposition, maritime traffic pollution, non-point breeding sources, domestic sewage pollution, and exploitation of coal and gold resources, etc.